Comparative Insecticide Application Techniques (Micro-Sprinkler) Against Drosophila suzukii Matsumura (Diptera: Drosophilidae) in Highbush Blueberry. Issue 2 (8th February 2022) - Mermer, Serhan; Tait, Gabriella; Pfab, Ferdinand; Mirandola, Enrico; Bozaric, Aleksandar; Thomas, Canessa D; Moeller, Maxwell; Oppenheimer, Katherine G; Xue, Lan; Wang, Lu; Walton, Vaughn M
Abstract: Drosophila suzukii (Matsumura), spotted-wing drosophila, is a major pest in small fruit crops including highbush blueberry. Controlling D. suzukii is challenging and chemical control is the main method to manage D. suzukii populations. Growers have expressed interest in using micro-sprinklers as an alternative method to apply insecticides. The current study aimed to evaluate if insecticide applications using micro-sprinklers can be used as an alternative method to protect the fruit from D. suzukii egg-laying. Modeling was used as an additional tool to parameterize the relative insecticide efficacy on oviposition. Field measurements of different treatments were conducted over periods of eleven days on commercial-standard highbush blueberry. Cyantraniliprole and spinetoram were applied using both a micro-sprinkler and a backpack sprayer. Treatments of Chromobacterium subtsugae and zeta-cypermethrin were only applied using a backpack sprayer. Both cyantraniliprole and spinetoram treatments resulted in moderate suppression of D. suzukii egg-laying. No statistical significance was found between micro-sprinkler and backpack sprayer applications for these two insecticides. Zeta-cypermethrin treatments using a backpack sprayer resulted in the most significant suppression of D. suzukii egg-laying over eleven days, while C. subtsugae was less effective at preventing D. suzukii egg-laying. Modeling simulations estimate the impact of the control methods on D. suzukii populations dynamics and simulation outputs indicated that backpack sprayers reduced D. suzukii populations at more pronounced levels compared to micro-sprinkler applications. The present study indicates that there is an underlying value of micro-sprinkler systems as an alternative and rapid spray application technique to help suppress D. suzukii pest populations during high-pressure periods in highbush blueberry production.